THE PRINCIPLES OF TEACHING ADULT - Tursunboeva Latofat Tukhtamurotovna (Web of Journals Publishing, 2024)
This article examines some innovative and effective approaches to adult education in the modern age, and modern adult education methods that prioritize individual learning experiences, active participation, and real-life application of concepts.
Keywords: teaching, methods, methodology, modern technologies, motivation, innovations, innovative methods, traditional education, teachers, educational programs, educational process, professional pedagogical competence.